Can Allosteric Receptor-Protein Interactions in Receptor Complexes Be a Molecular Mechanism Involved in Cancer Immune Therapy? - Borroto-Escuela, Dasiel O.; Fuxe, Kjell (Frontiers in Endocrinology, 2019)
Based on the work in the Central Nervous System with discoveries of allosteric receptor-receptor interactions in homo-and heteroreceptor complexes representing a major integrative mechanism in synapses and extrasynaptic regions, it is proposed that a similar mechanism exists in the immunological synapses. We discuss a putative additional molecular mechanism for the ability of the inhibitory T cell signaling proteins CTLA-4 and PD-1 and the adenosine A2AR to diminish T cell activation leading to enhancement of cancer development. We suggest that in the same immunological synapse involving T cells and antigen presenting cells multiple heteroreceptor complexes can participate and be in balance with each other. Their composition can vary between functional states and among different types of T cells. The T cell receptor (TCR) and its accelerators, strongly enhancing T cell activation, can be under inhibitory control by T cell signaling proteins CTLA4 and PD-1 and also the adenosine A2AR through inhibitory allosteric receptor-receptor interactions in different types of heteroreceptor complexes. As a result inhibitory tumor induced immunosuppression develops due to a dominance of the inhibitory signaling causing a brake on the TCR and/or its accelerator and the cancer immunotherapy becomes blocked.